Primary school teachers’ patterns in using communication-supporting strategies following a professional development program: lessons learned from an exploratory study with three teachers - Edlund, Karin; Kjellmer, Liselotte; Hemmingsson, Helena; Berglund, Eva (Frontiers in Education, 2023)
Oral language skills underpin later literacy achievement and life prospects, and many children struggle with oral language for various reasons. Hence, it is crucial for teachers to provide a learning environment with rich opportunities for all children to practice their oral language. The aim of this exploratory study was to explore a professional development (PD) programme designed to coach teachers in using communication-supporting strategies during verbal teacher-child interactions in regular classrooms. In focus were five strategies from the Communication Supporting Classroom Observation Tool (CSCOT). The study used a mixed-method case design with multiple observations across four time points over 10 weeks and a follow-up observation after two months. Outcome measures were collected at pre- and, post-intervention and at follow-up. The cases were two intervention teachers and one comparison teacher in second grade in Swedish primary schools. The teachers were directly observed and video-recorded during teacher-child structured small group conversations while discussing different texts with two groups of children each. The groups were mixed and comprised both children struggling with oral language as well as more typically developing children. To further understand the verbal interactions, the teachers’ amount of talk in relation to the children was analysed in terms of the percentage distribution of the total number of words per minute. The overall patterns of strategy use showed that the two intervention teachers applied more varied strategies from the PD programme during the intervention period, but this was not maintained at the follow-up. The amount of teacher talk appeared stable over time, with individual differences in the three teachers. We also discuss the teachers’ own insights and our experience in the design of the PD programme, which may guide future research and applications of the PD programme.